Breast cancer early detection: A phased approach to implementation. (29th April 2020) - Ginsburg, Ophira; Yip, Cheng‐Har; Brooks, Ari; Cabanes, Anna; Caleffi, Maira; Dunstan Yataco, Jorge Antonio; Gyawali, Bishal; McCormack, Valerie; McLaughlin de Anderson, Myrna; Mehrotra, Ravi; Mohar, Alejandro; Murillo, Raul; et al.
Abstract : When breast cancer is detected and treated early, the chances of survival are very high. However, women in many settings face complex barriers to early detection, including social, economic, geographic, and other interrelated factors, which can limit their access to timely, affordable, and effective breast health care services. Previously, the Breast Health Global Initiative (BHGI) developed resource‐stratified guidelines for the early detection and diagnosis of breast cancer. In this consensus article from the sixth BHGI Global Summit held in October 2018, the authors describe phases of early detection program development, beginning with management strategies required for the diagnosis of clinically detectable disease based on awareness education and technical training, history and physical examination, and accurate tissue diagnosis. The core issues address include finance and governance, which pertain to successful planning, implementation, and the iterative process of program improvement and are needed for a breast cancer early detection program to succeed in any resource setting. Examples are presented of implementation, process, and clinical outcome metrics that assist in program implementation monitoring. Country case examples are presented to highlight the challenges and opportunities of implementing successful breast cancer early detection programs, and the complex interplay of barriers and facilitators to achieving early detection for breast cancer in real‐world settings are considered. Abstract : Women in many settings face complex barriers to early detection, including social, economic, geographic, and other interrelated factors, which can limit her access to timely, affordable, and effective breast health care services. In this consensus manuscript, phases of an early detection program development are described, beginning with management strategies required for the diagnosis of clinically detectable disease, and core issues are described pertaining to successful planning, implementation, and the iterative process of program improvement needed for a breast cancer early detection program to succeed in any resource setting.